2019
DOI: 10.3389/fnbeh.2019.00078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noradrenergic Stimulation Upon Context-Related Extinction Learning Performance and BOLD Activation in Hippocampus and Prefrontal Cortex Differ Between Participants Showing and Not Showing Renewal

Abstract: While the neural structures mediating context-related renewal of extinction are well established, the neurotransmitter systems processing renewal remain elusive. Noradrenergic stimulation before extinction improved learning, but did not alter renewal. Since context processing already during initial conditioning can influence renewal, in this fMRI study we investigated how noradrenergic stimulation by a single dose of atomoxetine (ATO) before initial acquisition of a context-related predictive-learning task aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
1
14
1
Order By: Relevance
“…These unexpected results question whether and via what mechanism taVNS modulates the ability to learn changes in contingencies. In particular, the null effect of taVNS on reversal learning is in contradiction with previous studies showing a facilitating effect of atomoxetine in a similar predictive learning task (Lissek et al, 2015(Lissek et al, , 2019. The hypothesized noradrenergic mechanism cannot explain the observed difference in performance for the reversal relative to the distractor stimuli between the groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These unexpected results question whether and via what mechanism taVNS modulates the ability to learn changes in contingencies. In particular, the null effect of taVNS on reversal learning is in contradiction with previous studies showing a facilitating effect of atomoxetine in a similar predictive learning task (Lissek et al, 2015(Lissek et al, , 2019. The hypothesized noradrenergic mechanism cannot explain the observed difference in performance for the reversal relative to the distractor stimuli between the groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Such complexity may reduce the risk of ceiling effects at the beginning of the learning curve when the effect of taVNS can be expected to be maximal (Burger et al, 2016(Burger et al, , 2017Szeska et al, 2020). Lissek and colleagues developed a predictive learning task in which atomoxetine, a selective NA reuptake inhibitor, facilitated reversal learning in healthy humans (Lissek et al, 2015(Lissek et al, , 2019. Reversal learning can be conceptualized as a more complicated form of extinction learning (Goarin et al, 2018;Schiller & Delgado, 2010).…”
mentioning
confidence: 99%
“…The present results expand the findings from previous studies that too found-mainly incidental-iFG activation during extinction and recall (Lissek et al, 2015b;Klass et al, 2017;Lissek et al, 2019), by demonstrating for the first time differential activation of this region within the same individuals, depending on their momentary propensity to show renewal. This within-subject confirmation of previous between-subjects results highlights the important role iFG apparently has for processing renewal-related information.…”
Section: Inferior Frontal Gyrus Activation During Extinction Learningsupporting
confidence: 89%
“…Another prefrontal region potentially important for renewal is inferior frontal gyrus (iFG)-an area which in our previous studies was occasionally found activated during extinction learning and recall (e.g., Lissek et al, 2017Lissek et al, , 2019, and whose involvement in renewal is as yet unexplored. IFG is assumed to mediate response inhibition (Konishi et al, 1999), necessary during operant/instrumental extinction learning (Bouton et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive learning task used in this study is a modified version of a learning task that was designed to reliably evoke a renewal effect in context-related extinction learning without a fear component 30 . Previous studies already used this task in a different version adapted for fMRI experiments 4 , 5 , 19 , 32 , 39 . Participants were asked to put themselves in the position of a physician and predict whether various food items (fruit or vegetable) served in two different restaurants would lead to the aversive consequence of a stomachache in their patient.…”
Section: Methodsmentioning
confidence: 99%